Growth and Yield of Carrot (Daucus Carota L) as Affected by Planting Methods in a Derived Savannah Zone of Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Nigeria was conducted at the research farm of the Department of Crop Science and Horticulture, Nnamdi Azikiwe University, Awka, Nigeria Two planting methods were used (direct sowing, and transplanting) as treatments for the experiment, which was laid out in a Randomized Complete Block Design (RCBD) and replicated four times. Data was collected on the growth, yield, and root marketability parameters. All data collected were statistically analyzed using all outlined procedures. The results of the study showed no significant variation between the planting methods on the stem girth and leaf number at 4, 6, 8, 10, and 12 WAP and plant height at 12 WAP, while transplanting significantly varied (P<0.05) from direct sowing at 4, 6, 8 and 10 WAP. Planting methods did not influence the plant biomass, root length, number of roots harvested, fresh weight of leaves, fresh weight of roots, but were statistically similar. Transplanting influenced significantly the root diameter, while direct sowing also significantly influenced the harvest index and the root marketability parameters; root uniformity, marketable yield, and total marketable root yield%. From the results presented in the investigation, direct sowing had significant effect on root marketability, which is paramount in commercial carrot production. It is thereby recommended that for optimum carrot production and marketability, carrots should be directly sown.